KOMPARASI MODEL INKUIRI TERBIMBING MENGGUNAKAN EKSPERIMEN LABORATORIUM RIIL DAN VIRTUAL TERHADAP KETERAMPILAN PROSES SAINS SISWA - astri lliana asri; elvi yenti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This[u1] research was an experiment aiming at knowing the difference between the effect of Guided Inquiry model using Real and Virtual Laboratory Experiment on student science processes skill on Buffer material at State Senior High School Plus Riau Province in the Academic Year of 2016/2017. Samples of this research were the elevent grade student class MS 1 as the first experimental group amount 25 students taught by using Guided Inquiry model usig Real Laboratory Experiment and class MS 4 as the second experimental group amount 25 students taught by using Guided Inquiry Model using Virtual Laboratory Experiment. Simple random sampling was used in this research. Documentation and observation were the techniques of collecting the data. The preliminary and final data were analyzed by using Independent sample t-test. Based on the result the data processed, it was obtained that tobserved was 2.432 and ttabel was 1.671 revealing that tobserved was was higher than ttabel. Thus Ho was rejected. This research finding revealed that the use of Guided Inquiry model using Real and Virtual Laboratory Experiment on Buffer material. Kp formula was used to measure the effect of using Guided Inquiry model, and the coefficient effect was 10.96%.Keywords: Guided Inquiry Model, Real Laboratory, Virtual Laboratory, Science Processes Skill, Buffer